2021
DOI: 10.1177/00224278211030964
|View full text |Cite
|
Sign up to set email alerts
|

The Racial Divide at Micro Places: A Pre/Post Analysis of the Effects of the Newark Consent Decree on Field Inquiries (2015–2017)

Abstract: Objectives: An initial investigation by the Department of Justice (DOJ) found that the Newark Police Department (NPD) had engaged in a “pattern or practice” of constitutional violations with regard to stop and arrest practices, prompting the city to enter a consent decree. Methods: This study draws on official event-level data on FIs recorded by NPD officers (N = 50,322) and uses random effects panel regression models to examine how socioeconomic characteristics interact with the implementation of the consent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…There is some evidence that consent decrees and other forms of structural reform litigation have been effective in reducing misconduct (Rushin, 2015 ), but we do not know if consent decrees were an efficient or cost-effective mechanism for reform. Chillar ( 2021 : 7) conducted an extensive and thorough review of the evaluation research conducted on consent decrees and published an important article that concluded as follows: While some consent decree evaluations find compelling evidence regarding the outcomes used to track compliance and the positive impacts police and citizens experienced, it is important to note that the studies were conducted during the period in which the department was under consent decree or was recently released from federal oversight. This ensured that the departments had no time to revert to the problematic policies and practices that warranted the implementation of the consent decree.…”
Section: External Police Oversightmentioning
confidence: 99%
“…There is some evidence that consent decrees and other forms of structural reform litigation have been effective in reducing misconduct (Rushin, 2015 ), but we do not know if consent decrees were an efficient or cost-effective mechanism for reform. Chillar ( 2021 : 7) conducted an extensive and thorough review of the evaluation research conducted on consent decrees and published an important article that concluded as follows: While some consent decree evaluations find compelling evidence regarding the outcomes used to track compliance and the positive impacts police and citizens experienced, it is important to note that the studies were conducted during the period in which the department was under consent decree or was recently released from federal oversight. This ensured that the departments had no time to revert to the problematic policies and practices that warranted the implementation of the consent decree.…”
Section: External Police Oversightmentioning
confidence: 99%
“…Not surprisingly, during this 3-year period, Seattle, WA was in the process of entering a consent decree. We restricted the floor of our data period to 2014 to prevent introducing a historical event that may have impacted overall volumes of patrol and subsequent crime levels (e.g., Chillar, 2022;Powell, Meitl, & Worall, 2017). Second, the volume of CAD data from 2020-2022 was much lower than in years prior.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…There are some exceptions; for instance, Weisburd et al (2014) show that about 80% of New York City Police Department (NYPD) stops on street segments during 2009-2010 occurred in just 5% of New York City's street segments. In other cases, scholars have invoked the spatial concentration of enforcement without providing analogous estimates (Briggs & Keimig, 2017;Chillar, 2022;Wheeler, 2020;Wheeler et al, 2018). The descriptive question of how concentrated arrests are by place within cities has largely been unaddressed.…”
Section: Extending the Criminology Of Place Toward Race And Policingmentioning
confidence: 99%